Hypoglycemic activity of Sida spinosa Linn. root extract in normoglycemic rats - Ibrahim Shaikh; Preeti Kulkarni; Ankur Patel; Venkatrao Kulkarni (International Journal of Phytomedicine, 2011)
There is an increased demand of patients to use natural products with antidiabetic activity and ethnobotonical survey conducted revealed that Sida spinosa Linn. root is used in the treatment of diabetes. The present investigation aims to examine the hypoglycemic potential of Sida spinosa Linn. root in normal rats. The root of Sida spinosa Linn. was extracted using ethanol and water and tested for acute toxicity according to OECD 423 guidelines. The ethanolic (SSE) and aqueous (SSA) extracts at 200 and 400 mg/kg b.w. were screened for blood glucose lowering capacity in normal animals (18h fasted rat model) and Glibenclamide (GLB) was used as a standard. Serum glucose (SG) levels were estimated using a glucose oxidaseperoxidase reactive strips and a glucometer. The oral glucose tolerance test (OGTT) was carried out in normal rats. The results of acute toxicity showed that the animals had good tolerance to single doses of SSE/SSA in doses as high as 4000mg/kg and were non-lethal. In OGT test, the normoglycemic rats treated with higher dose SSE, SSA and GLB (10mg/kg) showed 30.36%, 25.24% and 33.21% reduction (P<0.001) in SG level respectively over the period of 120 min compared to normal control group. In single dose one day study, higher dose of SSE, SSA and GLB showed significant (p<0.001) reduction in SG levels (22.3%, 18.2% & 28.6% respectively) at 3h after oral administration. The ethanolic extract (400 mg/kg) was more effective in reducing the SG level in OGTT compared to aqueous extract with improved glucose tolerance. The root of Sida spinosa Linn. has potent hypoglycemic activity in normal rats justifying its use in indigenous system of medicine.